Assessing the Impact of Special Education Programs on Behavioral Issues in Children with Developmental Delays in Punjab, Pakistan - Ms Hadia Waseem; Ms Wajiha Saleem; Ms Nasira Bilal (`, 2025)
This research explores the effects of special education on behavioral problems among children with developmental delay in Punjab, Pakistan. The study contributes to a better understanding of the influence of attending Type VI school on major behavioral components, including aggression, hyperactivity, and social problems. One hundred children who were 5-12 years old and had a diagnosis of developmental delay participated in special education programs. Information on the participants was obtained with data derived through interviews and observations that involved teachers and parents or guardians. The results indicate significant decreases of aggressive behavior, hyperactivity and social withdrawal particularly among integrated programs, which stressed both academic and social support. Greater gains in behavior were also associated with receiving programs of longer duration. Parent involvement was one of the key aspects where children displayed more behavioral improvements when their parents were closely involved in their educative period. Furthermore, behavior management knowledge among teachers was found to be associated with improved behavioral results. These findings underscore the success of dyadic special education programs for children with developmental delays in addressing behavior problems. The study highlights the importance of increasing inclusion, training for teachers and involvement from parents to extend the benefits of special education programs in the area. Keywords Special Education, Developmental Delays, Behavioral Issues, Integration, Parental Involvement, Teacher Training